К вопросу о кодексе корпоративной социальной ответственности туристических компаний - Муратова, Л.Р.; Царенко, Н.В. (Культура народов Причерноморья, 2014)
Определено понятие «корпоративная социальная ответственность (КСО) туристических
компаний» в контексте разработки кодекса КСО. Обозначены организации, инициирующие соблюдение
норм КСО в сфере туризма. Рассмотрены нормативно-законодательные акты, регламентирующие
нормы КСО для туристических компаний. Обоснована целесообразность разработки и реализации в
деятельности туристических компаний Кодекса КСО, который бы учитывал интересы всех
заинтересованных сторон и устанавливал правила социально ориентированного ведения бизнеса. Визначено поняття «корпоративна соціальна відповідальність (КСВ) туристичних
компаній» в контексті розробки кодексу. Позначені організації, які ініціюють дотримання норм КСВ у
сфері туризму. Розглянуто нормативно-законодавчі акти, що регламентують норми КСВ для
туристичних компаній. Обґрунтовано доцільність розробки та впровадження в діяльність туристичних
компаній Кодексу КСВ, який би враховував інтереси всіх зацікавлених сторін і встановлював правила
соціально орієнтованого ведення бізнесу. The article considered the definition of "corporate social responsibility of tourism companies" as the
foreign and domestic policy, a set of practical activities and ongoing programs that are integrated into the
process of creating and providing tourism services and are based on social, environmental and economic
responsibility of travel companies to consumers and society. Allocated internal and external manifestations of
corporate social responsibility. Considered normative acts regulating external and internal standards of
corporate social responsibility for tourism companies. Identified gaps in the regulation of corporate social
responsibility in the existing regulatory and legislative acts. Highlighted the organizations that initiated the
development and application of standards of corporate social responsibility for the travel industry in the Russian
Federation. The advantages and disadvantages of compliance with corporate social responsibility activities of
travel agencies. The expediency of the development of the Code of corporate social responsibility and travel
companies, which would take into account the interests of all stakeholders, and establishes the rules of socially
oriented way of making a business.